Bentuk Penanganan Bawaslu Terhadap Pelanggaran Netralitas ASN - Aldan Syaifullah Alulu (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research aims to find out the role of Bawaslu in creating honest and fair elections in Gorontalo Province and how Bawaslu handles violations of ASN neutrality. In this research, the type of research used is normative-empirical research. This type of research is used because of the compatibility between theory and research methods that researchers need in preparing this research proposal. Bawaslu's role in creating honest and fair elections in Gorontalo province is: carrying out outreach and supervision. Bawaslu's form of handling violations of ASN neutrality is to conduct an inspection and forward it to the State Warden Apparatus Commission (KASN). In handling violations of ASN neutrality, Bawaslu receives reports from the public and makes recommendations to KASN if violations are found. "From KASN, a recommendation will then be made to the PPK (Personnel Development Officer). If the KASN recommendation is not implemented by the PPK, then BKN can make a penalty